Thermotherapy in treating fennel seeds (Foeniculum vulgare Mill.): effects on health and physiological quality - Gama, Juliana; Araújo Neto, Aderson; Alcântara Bruno, Riselane; Pereira Júnior, Lécio; Medeiros, José George (Revista Ciência Agronômica, 2014)
Thermotherapy is a physical treatment consisting of the exposure of seeds to the action of heat over time. The aim was to assess the health and physiological quality of fennel seeds (Foeniculum vulgare Mill.), both freshly harvested and stored for three years, and submitted to thermotherapy. Two experiments were conducted. In the first, thermotherapy was carried out on freshly-harvested fennel seeds obtained under different cropping systems: T1 - Monocrop fennel treated with the insecticide, thiamethoxam; T2 - Monocrop fennel without the application of insecticide; T3 - Fennel intercropped with cotton and treated with insecticide; T4 - Intercropped fennel without the application of insecticide. In the second experiment, seeds were used which had been stored for three years and obtained from plants, both treated and untreated with insecticide. The seeds were exposed to dry heat for different periods (0, 3, 6, 9, 12 and 15 days) at 70 °C. The tests performed included: health, germination, first count, speed germination index, seedling length and dry weight. The cropping systems had no influence on the incidence of the fungus Alternaria sp. Stored fennel seeds coming from plants treated with insecticide, display better health and physiological quality. A period of 12 days of thermotherapy is effective in controlling the fungus Alternaria sp. without causing losses in the viability of the fennel seeds.